Participatory Mapping of Village Potential with Geotagging Data (Case Study: Wedomartani Village, Sleman, Yogyakarta) - Pelly, Dandi Arianto; Wiyono, Maryadi Budi (BHUMI: Jurnal Agraria dan Pertanahan, 2021)
Digital spatial data has the highest demand, especially for the needs of analysis in terms of mapping. Mapping is currently the focus of attention of many institutions because real objects in the field in a wide range can be visualized in a precision field with a specif ic scale. Many villages do not have digital spatial data; one of them is Wedomartani village. Therefore, an inventory of digital spatial data of important village objects needs to be done. This study aims to map the potential of village using satellite imagery data from Google Earth and Geotagging photographs and determine the zoning potential of the Land Use of Wedomartani village. The method used to map the potential of villages using satellite imagery data is the method of interpretation, then geotagging photo data obtained through surveys utilizing GPS tag technology from smartphones and the participatory role of village communities. The determination of village land-use zoning used the matching method of the potential map with validation of geotagging photo data. The results interpretation of satellite images shows that the potential in the village of Wedomartani in the form of important objects as the potential of the village is public facilities, tourism objects, theme parks, sports facilities, buildings, roads, rivers, and agriculture. The zoning results of the potential land use of the Wedomartani village consist of Trade and Service Zones in the form of micro, small and medium businesses spread along the main road as a sector of economic potential (212.73 Ha); The Recreation Zone is in the form of Maguwoharjo Football Stadium, Jogja Bay Pirates Adventure Park Family Park, Tambak Boyo Reservoir and Gebang Temple Cultural Heritage Site as a potential tourism sector (23.48 Ha); Agricultural and Plantation Zones in the form of irrigated rice, maize and chili as potential for sustainable agriculture (661.19 Ha).